2015
DOI: 10.5897/jaerd2015.0672
|View full text |Cite
|
Sign up to set email alerts
|

Farmers knowledge, attitudes and perceptions of occupational health and safety hazards in Trinidad, West Indies and implications for the Agriculture sector

Abstract: Studies have shown that Trinidad has an aged farming population. Young persons are not entering the sector. As such, older farmers will continue to be the backbone of Trinidad's agricultural sector. There is urgent need for focus to be placed on improving the state of occupational health and safety within this sector. This study sought to determine farmers' knowledge, attitudes and perceptions towards occupational health and safety issues in agriculture and recommend actions to reduce/prevent health and safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…More than half (55.9%) of the participants said they apply pesticides on their farms thrice or more during one cropping season. The reuse of empty pesticide containers for other domestic activities is a common practice among farmers, especially in LMICs, as reported in previous studies [5,35,36]. This practice can present severe non-occupational exposure to pesticide residue considering the persistent nature of these chemicals, which can remain in the containers over a long period.…”
Section: Discussionmentioning
confidence: 89%
“…More than half (55.9%) of the participants said they apply pesticides on their farms thrice or more during one cropping season. The reuse of empty pesticide containers for other domestic activities is a common practice among farmers, especially in LMICs, as reported in previous studies [5,35,36]. This practice can present severe non-occupational exposure to pesticide residue considering the persistent nature of these chemicals, which can remain in the containers over a long period.…”
Section: Discussionmentioning
confidence: 89%
“…21.57% of respondents strongly agreed with this point of view [33]. To add to this majority (65%) of farmers negatively perceived because of not having ample technical support in agricultural practices Trinidad, West Indies [55]. Therefore, Saha et al [34] revealed that, raising awareness regarding the benefits of agroforestry practices as well as providing technical assistance.…”
Section: Discussionmentioning
confidence: 97%
“…Agroforestry can provide the next step in sustainable agriculture by promoting and implementing integrated, biodiversity processes [55]. However, the success of agroforestry practices is determined by the level of adoption of agroforestry by the farmers [34].…”
Section: Discussionmentioning
confidence: 99%
“…The recurrences of food-borne illness and diseases along with the current global COVID−19 pandemic have raised awareness of food safety issues among all the stakeholders, including producers, processors, retailers, and consumers. This has not only reduced consumers' confidence in food safety but also raised more significant concerns regarding the sustainability of the food industry and trade [1][2][3]. Production sustainability, environmental responsiveness, and animal welfare are core concerns globally, reflected in the United Nations Sustainable Development Goals (UN SDGs).…”
Section: Introductionmentioning
confidence: 99%